Empowering Religious Leaders for Sustainable Prevention of Lifestyle-Related Diseases - Elizabeth Sulastri Nugraheni; Hanna Tabita Hasianna Silitonga; Saskia Dyah Handari; Mellyanawati Mellyanawati; Stefani Nurhadi; Jennifer Tantadiputra; Rafkha Hakam Irsyad Maulana (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Promotive and preventive care represents the most meaningful contribution physicians can make within preventive medicine. However, this approach is often difficult to implement in clinical settings, where patients typically seek help only after illness has developed. Strengthening health literacy and promoting healthier lifestyles at the community level are therefore essential to preventing lifestyle-related non-communicable diseases before onset. This study explores the empowerment of religious leaders and Islamic scholars as key actors in community-based promotive and preventive health efforts. In Indonesia’s collectivist and high–power distance culture, religious figures hold influential positions, making them effective agents of change for health education and behavior transformation. A descriptive cross-sectional design was employed using secondary data from questionnaires administered during community engagement activities. Educational sessions addressed lifestyle and health issues across demographic groups. Twenty-three participants completed structured self-assessments, and program effectiveness was evaluated using pre- and post-test measures. Results demonstrated diverse demographic characteristics among participants. Post-intervention findings showed a 13.1% improvement in attitudes toward healthy lifestyle practices. Additionally, 47.82% of participants had a body mass index above the normal range. These findings highlight the potential of religious leaders as catalysts for sustainable, community-based preventive health practices.